Estudo de trialelias no marcador forense tpox e caracterização do terceiro alelo - Picanço, Juliane Bentes (2014)
Genotyping of polymorphic short tandem repeats (STRs) loci is widely used in forensic DNA analysis. STR loci eventually present tri-allelic pattern as a genotyping irregularity and, in that situation, the doubt about the tri-allele locus calculation can reduce the analysis strength. Alleles at the TPOX STR locus have 6 14 different numbers of a four-nucleotide (AATG) repeat motif arranged in tandem. Although tri-allelic genotypes are generally rare, the TPOX tri-allelic pattern has a higher frequency, varying widely among populations. Despite this, there are few accurate reports to disclose the nature of the TPOX third allele. In this work we performed two studies: In the first one we present data obtained from 45 individuals belonging to the same pedigree, in which there were cases of tri-allelic TPOX genotypes. The subjects were apparently healthy with a normal biological development. We noticed six tri-allelic cases in this family, and all of them were women. Karyotype analysis showed no occurrence of partial 2p trisomy. All the tri-allelic cases had the genotype 8 10 11, probably due to three copies of the TPOX STR sequence in all cells (Type 2 tri-allelic pattern). Based on previous data we assumed an allele 10 as the TPOX third allele. The pedigree analyses show evidence that the TPOX extra allele was an allele 10, it is placed far from the main TPOX locus, and that there is a potential linkage of the TPOX extra-allele-10 with one marker on Xq. This was the first study that included a large pedigree analysis in order to understand the nature TPOX tri-allelic pattern. In the second study, we investigate whether there is a single third-extra allele in the TPOX tri-allelic pattern, what it is, and where it is. We looked for TPOX tri-allelic subjects in 75,113 Brazilian families. Considering only the parental generation (mother+father) we had 150,226 unrelated subjects evaluated. From this total, we found 88 unrelated subjects with tri-allelic pattern in the TPOX locus (0.06%; 88/150,226). Seventeen percent of these subjects (15/88) presented heterozygosis with peak imbalance, which we describe as a derived category to Clayton s Type 2 tri-allelic pattern (a higher peak of double dose homozygote plus a regular sized peak). In this paper we presented detailed data from 66 trios (mother+father+child; with true biological relationships) where the tri-allelic pattern was observed in the mother or in the father. In 39 of these families (39/66; 59%) the third-extra TPOX allele was transmitted either from the mother or from the father to the child. Our evidence indicated an allele 10 as the thirdextra TPOX allele, and it is on the X chromosome. The present data, which support the previous hypothesis, improve the knowledge about tri-allelic pattern of TPOX CODIS' locus allowing the use of TPOX profile in forensic analyses even when with tri-allelic pattern. This evaluation is now available for different forensic applications